Simple Macroeconomics of Crypto Currency and the Political Economy of Monetary Policy in a Democracy - Sugata Marjit; Kausik Gupta (Center for Economic Studies and ifo Institute (CESifo), 2023)
The paper attempts to examine the macroeconomic implications of the coexistence of crypto currency with legal tender money in the context of a democratic country such as India. The paper shows that macroeconomic implications of crypto currency can be captured by a simple extension of the IS-LM model. The main potential political consequence emerges due to difficulty in implementation of monetary policy, especially prior to elections. The paper shows that if the share of crypto currency out of total money supply is high it is bound to impact on the efficacy of monetary policy. .The paper also examines the practical difficulties of legalizing crypto currency.
Keywords: E52; E58; E61; E63; 330; block chain; crypto currency; legal tender money; monetary policy